Reflection Symmetry in Physics - Arvind Kumar, (SCHOOL SCIENCE, 2025)
Arguments based on symmetry are quite common in Physics. Usually at the higher secondary stage, these involve spherical and axial symmetry. In this article, we discuss another interesting symmetry, the space reflection symmetry, that is less emphasised but can be easily incorporated in the school curriculum at that stage